Pure Tone Audiometry and Hearing Loss in Alzheimer's Disease: A Meta-Analysis - Kwok, Susanna S.; Nguyen, Xuan-Mai T.; Wu, Diana D.; Mudar, Raksha A.; Llano, Daniel A. (Frontiers in Psychology, 2022)
An association between age-related hearing loss (ARHL) and Alzheimer’s Disease (AD) has been widely reported. However, the nature of this relationship remains poorly understood. Quantification of hearing loss as it relates to AD is imperative for the creation of reliable, hearing-related biomarkers for earlier diagnosis and development of ARHL treatments that may slow the progression of AD. Previous studies that have measured the association between peripheral hearing function and AD have yielded mixed results. Most of these studies have been small and underpowered to reveal an association. Therefore, in the current report, we sought to estimate the degree to which AD patients have impaired hearing by performing a meta-analysis to increase statistical power. We reviewed 248 published studies that quantified peripheral hearing function using pure-tone audiometry for subjects with AD. Six studies, with a combined total of 171 subjects with AD compared to 222 age-matched controls, met inclusion criteria. We found a statistically significant increase in hearing threshold as measured by pure tone audiometry for subjects with AD compared to controls. For a three-frequency pure tone average calculated for air conduction thresholds at 500-1000-2000 Hz (0.5-2kHzPTA), an increase of 2.3 decibel hearing level (dB HL) was found in subjects with AD compared to controls (p = 0.001). Likewise, for a four-frequency pure tone average calculated at 500-1000-2000-4000 (0.5-4kHzPTA), an increase of 4.5 dB HL was measured (p = 0.002), and this increase was significantly greater than that seen for 0.5-2kHzPTA. There was no difference in the average age of the control and AD subjects. These data confirm the presence of poorer hearing ability in AD subjects, provide a quantitative estimate of the magnitude of hearing loss, and suggest that the magnitude of the effect is greater at higher sound frequencies.